Mediating role of immune cells in causal relationships between lipids and intracranial aneurysm - Jiang, Haodong; Zhang, Baowen; Li, Junjun; Jiang, Xiaobing (Chinese medical journal, 2025)
[1] There are inevitable confounding factors in the research design, thus the research conclusions cannot reveal the causal relationship between lipids, immune cells, and IAs. More importantly, it remains unclear whether immune responses mediate the relationship between lipids and IAs. [...]we performed a Mendelian randomization (MR) analysis, a method that can avoid the interference of confounding factors and determine the correct causal relationships. Recent studies have found that patients with increased dyslipidemia still have a high residual cardiovascular risk despite receiving standard statin therapy to lower cholesterol levels. The most prominent of these is the nuclear factor-κ-gene binding (NF-κB) pathway. [...]genetically determined increased CD27 levels in B cells may promote the risk of aneurysm rupture by enhancing NF-κB pathway activity.